2016
DOI: 10.1088/1612-2011/13/4/045801
|View full text |Cite
|
Sign up to set email alerts
|

Black phosphorus as broadband saturable absorber for pulsed lasers from 1μm to 2.7μm wavelength

Abstract: It attracts wide interest to seek universe saturable absorber covering wavelengths from near infrared to midinfrared band. Multilayer black phosphorus, with variable direct bandgap (0.3-2 eV) depending on the layer number, becomes a good alternative as a universe saturable absorber for pulsed lasers. In this contribution, we first experimentally demonstrated broadband saturable absorption of multilayer black phosphorus from 1 μm to 2.7 μm wavelength. With the as-fabricated black phosphorus nanoflakes as satura… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
80
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 178 publications
(81 citation statements)
references
References 25 publications
0
80
1
Order By: Relevance
“…More importantly, BP has a thickness-dependent direct energy bandgap from 0.3 eV (bulk) to 2.0 eV (single layer) [15], filling up the interval between the zero gap of graphene and large gap of TMDCs, which is of great importance to the optical applications. Up to now, the broadband BP saturable absorbers have been widely applied to pulsed lasers in a wide spectral range from visible to mid-infrared [16][17][18][19][20][21][22][23][24][25]. Specifically, in 2 m Q-switched fiber lasers, Wang et al reported a passively Q-switched Tmdoped fiber laser using a BP deposited microfiber, delivering the maximum pulse energy of 154 nJ [26]; Jiang et al deposited the BP powders onto a side-polished fiber and achieved Q-switched operation with the maximum pulse energy of 276 nJ [27].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, BP has a thickness-dependent direct energy bandgap from 0.3 eV (bulk) to 2.0 eV (single layer) [15], filling up the interval between the zero gap of graphene and large gap of TMDCs, which is of great importance to the optical applications. Up to now, the broadband BP saturable absorbers have been widely applied to pulsed lasers in a wide spectral range from visible to mid-infrared [16][17][18][19][20][21][22][23][24][25]. Specifically, in 2 m Q-switched fiber lasers, Wang et al reported a passively Q-switched Tmdoped fiber laser using a BP deposited microfiber, delivering the maximum pulse energy of 154 nJ [26]; Jiang et al deposited the BP powders onto a side-polished fiber and achieved Q-switched operation with the maximum pulse energy of 276 nJ [27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, BP is a highmobility semiconductor with a direct bandgap sensitivity depending on the number of layers from 0.3 (bulk) to 2.0 eV (single layer) that exactly fill the gap between the zero bandgap of graphene and the wide bandgap (1.0-2.0 eV) of TMDs [25] . The narrower bandgap of BP makes itself act as the SA, which has been used in a broader wavelength operation range of 4-0.8 μm [26,27] . In addition, like graphene, BP SA owns the same excellent nonlinear optical response and easy fabrication process [13,23] .…”
mentioning
confidence: 99%
“…In addition, like graphene, BP SA owns the same excellent nonlinear optical response and easy fabrication process [13,23] . Q-switching or mode locking in SSLs using graphenelike absorbers [9,15,16,18,20,21,26,27,[29][30][31][32][33][34][35] are listed in Table 1. These absorbers are made by growing nanomaterials by chemical vapor deposition and transferring themon a mirror or depositing them on the quartz substrate by the spin-coating method.…”
mentioning
confidence: 99%
See 2 more Smart Citations